Business Management Training in Improving Culinary Msme Enterprises - Hardana, Ali; Nasution, Jafar; Damisa, Arti; Nasution, Yuriani (PT FORMOSA CENDEKIA GLOBAL, 2024)
The number of Micro, Small and Medium Enterprises (MSMEs) is a large part of the economic implementation in totality. However, the growth of MSMEs related to technological advances is still not in line with expectations. The proportion of MSMEs that use online sales is still low. This is caused by many MSMEs who do not understand the technical procedures for online sales. The purpose of this activity is to develop MSME expertise in universal management, digital marketing and financial recording. The development and improvement carried out is in the form of developing skills in making marketing planning, digital marketing and understanding financial records so that they can be useful in developing businesses that will be run in the future. The training participants were 34 micro-enterprises, most of which were culinary businesses that were given the management training they needed. The result obtained from this activity is the occurrence of culinary fostered partners who are more advanced in managing and selling products online.